Iodine-131 Metaiodobenzylguanidine Therapy for Neuroblastoma: Reports So Far and Future Perspective - Daiki Kayano; Seigo Kinuya (The Scientific World Journal)
Neuroblastoma, which derives from neural crest, is the most common extracranial solid cancer in childhood. The tumors express the norepinephrine (NE) transporters on their cell membrane and take in metaiodobenzylguanidine (MIBG) via a NE transporter. Since iodine-131 (I-131) MIBG therapy was firstly reported, many trails of MIBG therapy in patients with neuroblastoma were performed. Though monotherapy with a low dose of I-131 MIBG could achieve high-probability pain reduction, the objective response was poor. In contrast, more than 12 mCi/kg I-131 MIBG administrations with or without hematopoietic cell transplantation (HCT) obtain relatively good responses in patients with refractory or relapsed neuroblastoma. The combination therapy with I-131 MIBG and other modalities such as nonmyeloablative chemotherapy and myeloablative chemotherapy with HCT improved the therapeutic response in patients with refractory or relapsed neuroblastoma. In addition, I-131 MIBG therapy incorporated in the induction therapy was proved to be feasible in patients with newly diagnosed neuroblastoma. To expand more the use of MIBG therapy for neuroblastoma, further studies will be needed especially in the use at an earlier stage from diagnosis, in the use with other radionuclide formations of MIBG, and in combined use with other therapeutic agents.